A conceptual model of litter breakdown in low order streams. Issue 1 (February 2015) - Graça, Manuel A. S.; Ferreira, Verónica; Canhoto, Cristina; Encalada, Andrea C.; Guerrero‐Bolaño, Francisco; Wantzen, Karl M.; Boyero, Luz
<x xml:space="preserve">Abstract</x> The detrital‐based food web of many streams and rivers plays a fundamental role in the cycling and retention of carbon and nutrients. However, we still need to understand which global mechanisms underlie the biogeochemical pathways that control energy transfer from the detrital pool through local food webs into nutrient and energy cycles and storage. Previous attempts to understand the variability in litter breakdown rates have included the search for latitudinal variation patterns and analysis of the influence of different factors. Here we complement those studies by developing a conceptual model to predict litter breakdown dynamics in low order streams. According to the model, litter breakdown rates and the relative role of microbial decomposers and shredder detritivores on this process are hierarchically governed by interactions between climate/hydrology and geology acting upon plant traits, nutrient and leaf availability to decomposers, and metabolism of microbial decomposers and shredders. The model explains variations in leaf litter breakdown rates and shredder abundance across large geographic areas, allowing the formulation of predictions of how anthropogenic pressures may affect litter breakdown rates.